Isolation, identification and characterization of regional indigenous Saccharomyces cerevisiae strains - Šuranská, Hana; Vránová, Dana; Omelková, Jiřina (Elsevier, 2016)
In the present work we isolated and identified various indigenous Saccharomyces cerevisiae strains and screened them for the selected oenological properties. These S. cerevisiae strains were isolated from berries and spontaneously fermented musts. The grape berries (Sauvignon blanc and Pinot noir) were grown under the integrated and organic mode of farming in the South Moravia (Czech Republic) wine region. Modern genotyping techniques such as PCR-fingerprinting and interdelta PCR typing were employed to differentiate among indigenous S. cerevisiae strains. This combination of the methods provides a rapid and relatively simple approach for identification of yeast of S. cerevisiae at strain level. In total, 120 isolates were identified and grouped by molecular approaches and 45 of the representative strains were tested for selected important oenological properties including ethanol, sulfur dioxide and osmotic stress tolerance, intensity of flocculation and desirable enzymatic activities. Their ability to produce and utilize acetic/malic acid was examined as well; in addition, H2S production as an undesirable property was screened. The oenological characteristics of indigenous isolates were compared to a commercially available S. cerevisiae BS6 strain, which is commonly used as the starter culture. Finally, some indigenous strains coming from organically treated grape berries were chosen for their promising oenological properties and these strains will be used as the starter culture, because application of a selected indigenous S. cerevisiae strain can enhance the regional character of the wines.

In the present work we isolated and identified various indigenous Saccharomyces cerevisiae strains and screened them for the selected oenological properties. These S. cerevisiae strains were isolated from berries and spontaneously fermented musts. The grape berries (Sauvignon blanc and Pinot noir) were grown under the integrated and organic mode of farming in the South Moravia (Czech Republic) wine region. Modern genotyping techniques such as PCR-fingerprinting and interdelta PCR typing were employed to differentiate among indigenous S. cerevisiae strains. This combination of the methods provides a rapid and relatively simple approach for identification of yeast of S. cerevisiae at strain level. In total, 120 isolates were identified and grouped by molecular approaches and 45 of the representative strains were tested for selected important oenological properties including ethanol, sulfur dioxide and osmotic stress tolerance, intensity of flocculation and desirable enzymatic activities. Their ability to produce and utilize acetic/malic acid was examined as well; in addition, H2S production as an undesirable property was screened. The oenological characteristics of indigenous isolates were compared to a commercially available S. cerevisiae BS6 strain, which is commonly used as the starter culture. Finally, some indigenous strains coming from organically treated grape berries were chosen for their promising oenological properties and these strains will be used as the starter culture, because application of a selected indigenous S. cerevisiae strain can enhance the regional character of the wines.
Isolation, identification and characterization of regional indigenous Saccharomyces cerevisiae strains
Keywords: Saccharomyces genus; Oenological properties; ITS-PCR-RFLP; Interdelta PCR typing; Species-specific primers; Saccharomyces genus; Oenological properties; ITS-PCR-RFLP; Interdelta PCR typing; Species-specific primers